Study on efficiency of purification of ammonia wastewater with perennial ryegrass - WANG Yuan-yuan; HE Yong; PAN Jin-ming (浙江大学学报. 农业与生命科学版)
Study on aquaculture wastewater treatment with botanical filters is a burgeoning field. Twelve botanical filters with 0.8 m2 ryegrass (Lolium perenne L.) were used to treat ammonia wastewater of 4 different concentration levels. The initial total ammonia nitrogen (TAN) concentration of wastewater were 21.10, 49.99, 107.46 and 145.96 mg·L-1, with the amounts of un-ionized ammonia (UIA) corresponded to 14.3, 40.1, 91.7 and 125.2 mg·L-1, respectively. After about one-day (22 h) treatment, results showed that TAN concentrations declined by 20.94, 45.39, 49.99, and 49.3 mg· L-1, and UIA declined by 14.3, 40.1, 90.78, and 103.66 mg · L-1. It was also found that the UIA concentration had a significant effect on the growth of grass. At the end of the trial, the height of grass in group G1, G2, G3 and G4 were 32.28, 31.25, 19.85, and 17.48 cm respectively, with a fresh mass of 1.86, 1.71, 0.49, and 0.24 kg·m-2, and a dry mass of 0.21, 0.19, 0.06, and 0.04 kg·m-2. The research provided foundation for purifying ammonia wastewater with ryegrass.